All-American Apple Pie or Chocolate Sundae: A Cyber-Environment for Adult Education - Mark Federman; Marilyn Laiken (Adult Education Research Conference, 2007)
Conventional cyber-education environments do not actualize adult education principles. A design that implements Grace’s (1998) Theory of Adult Learning Community is demonstrated.